2005
DOI: 10.1099/jmm.0.46077-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of the cytolethal distending toxin of Actinobacillus actinomycetemcomitans on co-cultures of human oral cells

Abstract: The periodontal pathogen Actinobacillus actinomycetemcomitans expresses a cytolethal distending toxin (CDT) that typically arrests the growth of eukaryotic cells at either the G 0 /G 1 or G 2 /M phase of the cell cycle. It was previously found that CDT failed to arrest the growth of human periodontal ligament fibroblasts (HPLFs) when grown in pure culture. In contrast, proliferation of an oral epithelial cell line was rapidly inhibited by the toxin. In this study, the feasibility of using mixed-cell cultures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…4B and inset, respectively). These results were consistent with those of previous studies in which primary periodontal ligament fibroblasts were found to be resistant to the cell-cycle-inhibitory activity of the Cdt (Kang et al, 2005;Kanno et al, 2005).…”
Section: Effect Of the Cdt On Primary Gingival Epithelial Cells And Fsupporting
confidence: 95%
See 2 more Smart Citations
“…4B and inset, respectively). These results were consistent with those of previous studies in which primary periodontal ligament fibroblasts were found to be resistant to the cell-cycle-inhibitory activity of the Cdt (Kang et al, 2005;Kanno et al, 2005).…”
Section: Effect Of the Cdt On Primary Gingival Epithelial Cells And Fsupporting
confidence: 95%
“…Cultured HGF exhibited a morphology typical of fibroblasts and bound the CD90/Thy-1 (Ab-1) antibody. We previously showed that the Ab-1 marker is expressed by oral fibroblasts but not by immortalized labial epithelial cells (Kang et al, 2005).…”
Section: Effect Of the Cdt On Primary Gingival Epithelial Cells And Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Cdt holotoxin induces arrest in the G 2 phase of the cell cycle in a variety of proliferating cells, including epithelial cells, fibroblasts, human periodontal ligament cells, and lymphocytes (2,3,5,8,19,20,24,25,27,28,38,41). Interestingly, Shenker et al reported that the specific activity of Cdt against stimulated primary T lymphocytes was five-to 10-fold greater than that against HeLa cells (39) and subsequently showed that the Jurkat T-cell line is hypersensitive to Cdt intoxication (36).…”
mentioning
confidence: 99%
“…AactCDT has been shown to induce cell cycle arrest in the oral epithelial cell line GMSM-K [187,188], and in some studies also in human periodontal ligament fibroblasts (HPLFs) and human gingival fibroblasts (HGFs) [183,189], although the effects on this cell type have not been consistently reproducible [187,190]. The discrepancy may be due to the amounts of active toxin used in the studies, which may trigger a different set of responses in the target cells, depending on the efficiency of uptake and intracellular trafficking route.…”
Section: Periodontitismentioning
confidence: 99%